Teaching Speaking Eighth Grade Students of Junior High School through Drama Technique - Utami, Yulia; Johan, Andrian Nuriza (Scripta : English Department Journal, 2020)
The aim of this study is to find out whether the use of drama is effective or not in teaching speaking at the eighth grade of State Junior High School (SMPN) 1 Pejagoan in the academic year of 2017/2018. In this study , the two classes of the eighth grade were taken as the population and sample of SMP N 1 Pejagoan in the academic year of 2017/2018. There were 60 students taken as the samples . The data analysis techniques employed were descriptive and inferential analysis. The formula of t-test was applied to prove whether it is effective or not. After analyzed the data, the researcher found that the students’ achievement of experiment group was better than control group. The means score of experimental group was 85.60 and the means score of control group was 73.73, it could be seen from the final result of t-test analysis which stated that t-value was higher than t-table (7.54>2.00). Therefore, it can be conclude that the use of Drama Technique in teaching speaking at the eighth grade of SMP N 1 Pejagoan in the academic year of 2017/2018 is effective.